2020
DOI: 10.1016/j.algal.2019.101732
|View full text |Cite
|
Sign up to set email alerts
|

Improved production of lutein and β-carotene by thermal and light intensity upshifts in the marine microalga Tetraselmis sp. CTP4

Abstract: The industrial microalga Tetraselmis sp. CTP4 is a promising candidate for aquaculture feed, novel food, cosmeceutical and nutraceutical due to its balanced biochemical profile. To further upgrade its biomass value, carotenogenesis was investigated by testing four environmental factors, namely temperature, light intensity, salinity and nutrient availability over different growth stages. The most important factor for carotenoid induction in this species is a sufficient supply of nitrates leading to an exponenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 31 publications
4
36
0
1
Order By: Relevance
“…Furthermore, the lutein content of Nephroselmis sp. at up to 7.97 ± 0.84 mg g −1 DW was within the upper range values reported for lutein-producing strains, ranging between 0.5 and 9.6 mg g −1 DW [ 79 , 80 , 81 , 92 , 93 , 94 ]. However, further work on culture conditions is necessary to improve the biomass productivity, and thus the lutein productivity, in order to reach the levels reported in previous studies (up to 4.9 mg L −1 day −1 ) [ 79 , 81 , 95 , 96 , 97 ].…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, the lutein content of Nephroselmis sp. at up to 7.97 ± 0.84 mg g −1 DW was within the upper range values reported for lutein-producing strains, ranging between 0.5 and 9.6 mg g −1 DW [ 79 , 80 , 81 , 92 , 93 , 94 ]. However, further work on culture conditions is necessary to improve the biomass productivity, and thus the lutein productivity, in order to reach the levels reported in previous studies (up to 4.9 mg L −1 day −1 ) [ 79 , 81 , 95 , 96 , 97 ].…”
Section: Discussionsupporting
confidence: 82%
“…Zhao et al [48] examined the marine microalga Chlamydomonas sp. JSC4 under different environmental conditions for lutein production and concluded that the optimal lutein content was obtained under blue light and a lower temperature of 20-25 • C. Schüler et al [49] also examined different environmental factors on marine microalga Tetraselmis sp. CTP4 for carotenoid biosynthesis and examined that lutein amount increased 1.5-fold under higher light intensities (170 and 280 µmol photons m −2 s −1 ), but in contrast to Zhao et al [48], found a temperature increase from 20 to 35 • C, after only two days at a light intensity of 170 µmol photons m −2 s −1 , yielded the highest lutein productivity (3.17 ± 0.18 mg g −1 dry weight biomass).…”
Section: Microalgae Cultivation For Commercial Lutein Production and mentioning
confidence: 99%
“…Various studies have been reported to recover lutein from plants such as carrot, spinach and kale [ 13 , 14 , 15 ]. However, it is difficult to obtain lutein from plants because of existing small amounts in plants [ 16 ]. Microalgae such as Chlorella fusca (4.5 mg/g), Tetracysis aplanosporum (5.9 mg/g) and Chlorococcum citroforme (7.4 mg/g) have a higher lutein content than vegetables such as kale (0.03 mg/g), broccoli (0.04 mg/g) and cilantro (0.08 mg/g) and have a 5 to 10 times higher growth rate than plants; thus, various studies have been conducted to produce lutein from microalgae such as Tetraselmis sp., Chlorella sp.…”
Section: Introductionmentioning
confidence: 99%